Adherence to COVID-19 protocols: A comparative study of public and private hospitals in Ghana - Mohammed A. Issah; Roger A. Atinga; Anita A. Baku (Elsevier, 2024)
Objective: This study aimed to comparatively examine how public and private hospitals adhered to the COVID-19 safety protocols, and the factors associated with, and barriers to adherence in Ghana. Study design: A case study design drawing on quantitative and qualitative methods to determine adherence to, and barrier of adherence to the COVID-19 protocols. Method: A sample of 283 staff participated in the quantitative study, while in-depth interviews were conducted among management staff across the public and private hospitals. Data were analyzed using descriptive statistics, independent t-test to compare differences in adherence and logistic regression model to identify the factors associated with adherence to the COVID-19 protocols. Results: The regression results showed that adherence to the COVID-19 protocols in public and private hospitals were significantly associated with staff training on adherence in public (OR = 2.08; p < 0.01) and private (OR = 1.44; p < 0.05), and knowledge on adherence in public (OR = 3.12; p < 0.01) and private (OR = 11.45; p < 0.01) hospitals. Adherence to the protocol varied significantly between public and private hospitals (0.001 > p < 0.05), with an effect size ranging from small to large. Clients' behavioural factors and poor stocking of PPEs due to financial challenges were reported as barriers to adherence in both hospital types. Conclusion: Adherence to the COVID-19 protocols was more pronounced in public hospitals than private hospitals suggesting the need for interventions targeting the latter to promote client and staff safety.